Fotos, fachadas e personas: a construção identitária por meio do uso do aplicativo Instagram - Coelho, Pietro Giuliboni Nemr (2016)
The digital environment of social networks and apps allows the users to produce and share original contents in real time, to several people around the world. In the Instagram app, through material and symbolic consumption, users take possession of cultural symbols and signs to produce photos about the most diverse themes and to build their profiles inside a collaborative and dynamic environment. The research here presented had as an objective to study this process of imagery production and how it relates to the identity construction of the users in the digital environment, by snipping moments of their lives and the construction of facades. Supported by authors such as Castells, Giddens, Goffman, Primo, Silva, Slater and Tondato, we discussed the operation of the app and how it relates to the concepts of identity and consumption in a Post-Modern society; and based on interviews with users of the app, we develop the discussion about the construction of profiles and the possible implications to the image of each user. The results show us how Instagram becomes a stage, where users can build a facade by snipping moments of their daily activities, showing an ideal lifestyle, through the consumption of products and services portrayed in the pictures, even if its done unintentionally. Façade that is accessible to a more restrict audience than in other social networks.